Optimization of Slaughter Age of Jamuna Basin Lamb Based on Carcass Traits and Meat Quality (SAARC Journal of Agriculture, 2022)
The aim of this study was to identify optimum slaughter age on carcass traits and meat quality of Jamuna basin lambs. Thirty lambs were divided into three age groups like T1 (6 months), T2 (9 months) and T3 (12 months) having ten lambs of each treatment. Parameters studied were carcass traits, proximate component (DM, CP, EE, and Ash), physicochemical (Ultimate pH, cooked pH, cooking loss, drip loss, water holding capacity-WHC), sensory attributes (color, flavor, tenderness, juiciness, overall acceptability) and instrumental color values (L*, a* and b*). Hot carcass weight and dressing% were found significantly (p